Students’ Perceptions of Pedagogical Training Problem at Ho Chi Minh City University of Technology and Education - Dang, Thị Diệu Hiền; Bui, Thị Bích; Nguyen, Như Khương (Journal of Technical Education Science, 2023)
Technical pedagogy programme in training curriculum of Ho Chi Minh City University of Technology and Education (HCMUTE) had been trained since its establishment. However, in recent years, by many reasons, this programme has been stopped training for formal students. With the desire to find out HCMUTE students’ perspectives on technical pedagogical training in the university, the research was conducted to clarify five main contents related to technical pedagogy, including: (1) Students' perception of pedagogical training issues in the university; (2) The necessity of the pedagogical field at work as well as life in the future, the student's passion and desire for job opportunities related to pedagogy; (3) The students' willingness to study pedagogy; (4) The difference between in students’ pedagogical passion as well as willingness to study pedagogy programes with the school years and training systems; (5) The difference between the students’ pedagogical passion with willingness to study pedagogy programes, desire for job opportunities related to pedagogy to propose the future direction for pedagogy field at the University. The results of the analysis data that collected from 1,601 students who is studying at the university indicate that there is a difference in the selection rate at different levels with the content of the research, but there is no difference between the pedagogy passion, willingness to study pedagogy programes with the school years and training systems. There are about 30% to 50% of students ready to study pedagogy, especially a group of students who are passionate about pedagogy. Furthermore, the study also proposes some recommendations to find out suitable solutions in training the technical pedagogy field at the University in the future.